2020
DOI: 10.7150/jbji.44116
|View full text |Cite
|
Sign up to set email alerts
|

An Adjunct Indicator for the Diagnosis of Fracture-Related Infections: Platelet Count to Mean Platelet Volume Ratio

Abstract: Abstract. Introduction: Fracture-related infection (FRI) is a common complication associated with orthopaedic fracture care. Diagnosing these complications in the preoperative setting is difficult. Platelets are a known acute phase reactant with indices that change in accordance with infection and inflammation. The purpose of our study was to assess the diagnostic utility of platelet indices at assessing FRI.Methods: A retrospective review performed for all patients who underwent revision surgery for fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition to D-dimer, Zhao et al [ 47 ] noted that interleukin-6 (IL-6) had similar diagnostic value for FRI, with comparison to ESR and CRP. Other analyzed indicators for FRI diagnosis included platelet count to mean platelet volume ratio [ 48 ], wound alpha defensin [ 49 ], and cluster of differentiation (CD) 64 [ 50 ]. It is interesting that even altered gut microbiota can be considered as an auxiliary indicator for FRI diagnosis [ 51 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In addition to D-dimer, Zhao et al [ 47 ] noted that interleukin-6 (IL-6) had similar diagnostic value for FRI, with comparison to ESR and CRP. Other analyzed indicators for FRI diagnosis included platelet count to mean platelet volume ratio [ 48 ], wound alpha defensin [ 49 ], and cluster of differentiation (CD) 64 [ 50 ]. It is interesting that even altered gut microbiota can be considered as an auxiliary indicator for FRI diagnosis [ 51 ].…”
Section: Diagnosismentioning
confidence: 99%
“…17,18 Strony et al reported that the diagnostic accuracy of PVR in patients with fracture-related infection was no less signi cant than that of ESR or CRP, suggesting that PVR could function as an auxiliary diagnostic biomarker of fracture-caused infection. 19 The PLR and NLR have been found to have good diagnostic value for predicting surgical site infection, while the MLR and NLR demonstrate signi cant variation in feverish patients due to bacterial infections. [17][18][19] Based on the above research, a retrospective study conducted by Shi et al revealed that the PLR and NLR in the PJI group were signi cantly greater than those in the aseptic loosening (AL) group.…”
Section: Introductionmentioning
confidence: 99%
“…19 The PLR and NLR have been found to have good diagnostic value for predicting surgical site infection, while the MLR and NLR demonstrate signi cant variation in feverish patients due to bacterial infections. [17][18][19] Based on the above research, a retrospective study conducted by Shi et al revealed that the PLR and NLR in the PJI group were signi cantly greater than those in the aseptic loosening (AL) group. However, Shi did not evaluate the diagnostic ability of PVR or the MLR for predicting PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that changes in the PLR, PVR, NLR and MLR are closely related to inflammatory or infectious status in the body [ 13 , 14 ]. It is reported that the diagnostic accuracy of PVR in patients with fracture-related infection was no less significant than that of ESR or CRP, suggesting that PVR could function as an auxiliary diagnostic biomarker of fracture-caused infection [ 15 ]. The PLR and NLR have been found to have good diagnostic value for predicting surgical site infection, while the MLR and NLR demonstrate significant variation in feverish patients due to bacterial infections [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the diagnostic accuracy of PVR in patients with fracture-related infection was no less significant than that of ESR or CRP, suggesting that PVR could function as an auxiliary diagnostic biomarker of fracture-caused infection [ 15 ]. The PLR and NLR have been found to have good diagnostic value for predicting surgical site infection, while the MLR and NLR demonstrate significant variation in feverish patients due to bacterial infections [ 13 15 ]. A retrospective study also revealed that the PLR and NLR in the PJI group were significantly greater than those in the aseptic loosening (AL) group [ 16 ].…”
Section: Introductionmentioning
confidence: 99%